STRATEGI PENINGKATAN PROFIT PADA RUMAH MAKAN PATINKU MELALUI RE-DESIGN PACKAGING - Thang, John; Desipriani, Desipriani (Institut Seni Indoensia Surakarta, 2020)
Rumah Makan Patinku is one of the restaurants in Medan that has an interesting characteristic of patin fish as special culinary preparations. Rumah Makan Patinku previously had some packaging before, but the restaurant owner thought that it had not gotten the maximum sales profit increase. Sales increased from the previous package by 15% while the owner wanted an increase in profit of 50%. Through the re-design packaging and the addition of others packaging designs, it is expected to realize an increase in sales profit of Rumah Makan Patinku as expected by the owner. This design phase uses qualitative research methods and SWOT analysis methods. The results of the design in the form of patin bakar packaging, patin goreng packaging, gembung bakar packaging, packaging for rice can also be for roast chicken, and paper cups for hot drinks such as: hot tea and hot coffee.Abstrak Rumah Makan Patinku adalah salah satu rumah makan di Medan yang memiliki karakteristik ikan patin sebagai sajian kuliner spesial. Rumah Makan Patinku sebelumnya memiliki beberapa kemasan sebelumnya, tetapi menurut pemilik rumah makan kurang memberikan peningkatan keuntungan penjualan. Profit penjualan meningkat dari kemasan yang dirancang sebelumnya sebesar 15% sementara pemilik menginginkan peningkatan laba 50%. Melalui re-design packaging dan penambahan desain kemasan lainnya, diharapkan dapat mewujudkan peningkatan profit penjualan Rumah Makan Patinku seperti yang diharapkan oleh pemiliknya. Tahap perancangan ini menggunakan metode penelitian kualitatif dan metode analisis SWOT. Hasil perancangan berupa kemasan patin bakar, kemasan patin goreng, kemasan gembung bakar, kemasan untuk nasi putih juga bisa untuk ayam bakar, dan paper cup untuk minuman panas seperti: teh panas dan kopi panas.